2012
DOI: 10.1128/mcb.06152-11
|View full text |Cite
|
Sign up to set email alerts
|

TIEG1 Inhibits Breast Cancer Invasion and Metastasis by Inhibition of Epidermal Growth Factor Receptor (EGFR) Transcription and the EGFR Signaling Pathway

Abstract: TIEG1 can induce apoptosis of cancer cells, but its role in inhibiting invasion and metastasis has not been reported and is unclear. In this study, we find that decreased TIEG1 expression is associated with increased human epidermal growth factor receptor (EGFR) expression in breast cancer tissues and cell lines. TIEG1 plays an important role in suppressing transcription of EGFR by directly binding to the EGFR promoter. While overexpression of TIEG1 attenuates EGFR expression, knockdown of TIEG1 stimulates EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 38 publications
2
53
0
Order By: Relevance
“…Previously, it was reported that KLF10 functions to repress transcription at least in part by interacting with co-repressors such as histone deacetylases and recruiting them to target genes (47). We therefore examined HDAC1 occupancy at the SNAI2 promoter in control or KLF10-depleted A549 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was reported that KLF10 functions to repress transcription at least in part by interacting with co-repressors such as histone deacetylases and recruiting them to target genes (47). We therefore examined HDAC1 occupancy at the SNAI2 promoter in control or KLF10-depleted A549 cells.…”
Section: Resultsmentioning
confidence: 99%
“…HDACs have been frequently found to be associated with tumor development (56). Interestingly, KLF10 was shown to recruit corepressors like HDAC1 to its target genes to regulate their expression (47). In our study, we demonstrate that KLF10 recruits HDAC1 to the SNAI2 promoter and leads to decreased levels of H3K9ac and H3K27ac marks, providing a novel molecular insight behind KLF10 and its transcriptional regulation of EMT.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that the over-expression of TIEG1 is correlated with tumor development. The expression of TIEG1 was increased in malignant tumor tissues, including breast, pancreatic, and liver cancers, among others (Jiang et al, 2011;Jiang et al, 2012;Jin et al, 2012;Song et al, 2012). Various anticancer drugs that upregulate the expression of TIEG1 to induce cell apoptosis have been used to treat leukemia (Jin et al, 2004;Dosen-Dahl et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…KLF10 functions as a toggle by differential coupling of Sin3-histone deacetylase and P300/PCB-associated factor to integrate antagonistic signals regulating FOXP3, resulting in immune activation, and it also can directly bind to the TGF-β RII promoter in CD8(+)T cells, leading to enhanced gene expression and tumor immune response. KLF10 can inhibit breast cancer invasion and metastasis by inhibiting epidermal growth factor receptor (EGFR) transcription and the EGFR signaling pathway [29]. The expression of KLF10 is inversely correlated with pancreatic cancer stage, prognosis and overall survival [30].…”
Section: Discussionmentioning
confidence: 99%